Analytical tools for forecasting financial insolvency and potential bankruptcy of a company - CHERNYAVSKAYA, SVETLANA ALEXANDROVNA; ROSHCHEKTAEVA, ULIANA YURYEVNA; AKASHEVA, VALENTINA VYACHESLAVOVNA; KITIEVA, MALIKA IBRAGIMOVNA; DZODZIEVA, FATIMA NIKOLAEVNA (The journal of contemporary issues in business and government, 2021)
The activity of any company is a complex and multifaceted process. The company interacts with actors at different levels, from suppliers to the state, while throughout the entire operation of the organization, both external and internal ever-changing conditions affect its activity. Such an ever-changing environment puts companies at risk of an economically unstable state. Bankruptcy of a company is a crisis state that requires special methods of financial management to overcome it. It is very important to assess the state of the organization, take measures to restore solvency, and determine the probability of bankruptcy. Assessment and analysis of the probability of bankruptcy provides a general assessment of the financial stability of the company, its solvency, and a forecast for the future. The relevance of the research is due to a number of reasons: - in the modern Russian economy, the key problem is the crisis of non- payments; - in the context of the growing insolvency of Russian business entities, measures to prevent crisis situations, as well as measures aimed at restoring the solvency of the organization and stabilizing the financial condition, are of particular importance. All this, in our opinion, indicates the relevance of this study, the practical significance of the results obtained.